Novel T‐cell epitopes on Schistosoma japonicum SjP40 protein and their preventive effect on allergic asthma in mice. Issue 5 (23rd April 2016) - Ren, Jiling; Hu, Lizhi; Yang, Jing; Yang, Liang; Gao, Fei; Lu, Ping; Fan, Mengyu; Zhu, Yunjuan; Liu, Junyan; Chen, Lingling; Gupta, Shimpy; Yang, Xi; et al.
Abstract : We identified T‐cell epitopes on SjP40 protein using overlapping peptides, which could restimulate splenocytes from Schistosoma japonicum infected mice to produce IFN‐γ. Immunization with those epitope peptides could reduce the development of Th2‐like cytokine response, airway eosinophilic inflammation, mucus production, and allergen‐specific IgE in a mouse model of allergic asthma. Abstract : Allergic asthma is a chronic inflammatory disease mediated by Th2 cell immune responses. Currently, immunotherapies based on immune deviation are attractive, preventive, and therapeutic strategies for asthma. Many studies have shown that intracellular bacterial infections such as mycobacteria and their components can suppress asthmatic reactions by enhancing Th1 responses, while helminth infections and their proteins can inhibit allergic asthma via immune regulation. However, some helminth proteins such as SmP40, the major egg antigen of Schistosoma mansoni, are found as Th1 type antigens. Using a panel of overlapping peptides, we identified T‐cell epitopes on SjP40 protein of Schistosoma japonicum, which can induce Th1 cytokine and inhibit the production of Th2 cytokines and airway inflammation in a mouse model of allergic asthma. These results reveal a novel form of immune protective mechanism, which may play an important role in the modulating effect of helminth infection on allergic asthmatic reactions.